Social inequalities and prevalence of depressive symptoms: a cross-sectional study of women in a Mexican border city, 2014 - Alheli Calderon-Villarreal; Oscar J. Mujica; Ietza Bojorquez (Pan American Health Organization, 2020)
Objective. To assess the association between intersectional disadvantage and clinically significant depressive symptoms (CSDS), describing the magnitude of social inequalities in the prevalence of symptoms among adult women in Tijuana, Mexico. Methods. This was a cross-sectional study. CSDS were assessed using the Centers for Epidemiological Studies Depression Scale among a probability sample of 2 345 women from 18 - 65 years of age in 2014. CSDS prevalence was calculated according to categories of three social stratifiers: socioeconomic status (SES), educational attainment, and fertility (number of children). Social inequality was measured with the slope index of inequality (SII) and the concentration index (CIx). Intersectionality among stratifiers was explored descriptively and with multivariable regression analysis. Results. CSDS prevalence was 17.7% (95%CI: 15.1% - 21.0%). The SII and CIx showed inequity in all social stratifiers. The absolute difference in CSDS prevalence between the lowest and highest ends of the SES gradient was 21.9% (95%CI: 21.5% - 22.4%). Among the most disadvantaged women, i.e., those at the intersection of lowest SES, lowest educational attainment, and highest fertility, the CSDS prevalence was 39.5% (95% CI: 26.0% - 52.9%). Conclusions. Disadvantage along multiple axes was associated with CSDS. Efforts to improve the mental health of women should include equity-oriented policies that address its social determinants.